Design of High-Durability Superhydrophobic Microsurface Structures - Kang, Yousung; Jang, Gayun; Kim, Ga Eul; Kwon, Sin; Lee, Moon G.; Jeon, Yongho (International Journal of Precision Engineering and Manufacturing, 2022)
The development of industrial technology has increased the demand for surface modification to functionalize product surfaces. Superhydrophobicity affords a self-cleaning ability and is highly regarded in various industrial fields. However, superhydrophobic surfaces are limited in terms of their mechanical and chemical durability, which must be addressed to allow them to advance to the commercialization stage. In this study, we proposed a hierarchical structure to increase the durability of a microsurface exhibiting superhydrophobicity. It was optimized based on a design of experiments and finite element analysis. Results of the finite element analysis indicated that the maximum stress of the proposed hierarchical structure reduced by approximately 71% compared to that of the well-known pillar structure. The wettability and durability of the superhydrophobic film fabricated via micro three-dimensional printing and ultraviolet-imprint lithography were evaluated. The optimal hierarchical structure yielded a contact angle of 150° or more, and the change in the contact angle change was within 5° even after 10,000 cycles of the abrasion test.
Keywords: Abrasion tests; Finite element analyse; Hierarchical structures; High durability; Mechanical durability; Pin on disk; Pin on disk abrasion test; Projection micro-stereolithography; Superhydrophobic; Superhydrophobicity; Design of experiments; Mechanical durability; Pin on disc abrasion test; Projection microstereolithography; Superhydrophobic